PENGEMBANGAN KAWASAN RUMAH TENUN SAMBAS DI DESA SUMBER HARAPAN KABUPATEN SAMBAS - Tasya Nur Basitha; Affrilyno Affrilyno; Zairin Zain (JMARS: Jurnal Mosaik Arsitektur, 2022)
Sambas Regency is a local government that still follows the traditions, customs, and cultures of the past until now. Traditional ceremonies such as weddings and haircuts in Sambas Regency still use woven fabrics as clothing and complements. Sambas woven fabric is a traditional craft that is no less competitive with other regional woven products. The production of Sambas woven fabrics is currently carried out at the Weaving House in the village of Sumber Harapan, Sambas Regency, West Kalimantan. However, there are several problems in producing this woven fabric. Existing problems such as the weaving process which is still less productive, lack of product marketing, exhibitions that are held irregularly, lack of a place to show off woven products and lack of forums for discussion. This design uses the concept of contemporary architectural principles as an approach that supports the design of spaces that have innovative, creative and flexible themes. The shape changes in the design of the Sambas Weaving House Area are linear, almost symmetrical to add aesthetics to the area. The number of floors that are only designed in one floor because the building is a wide span. The design for the development of the Sambas Weaving House Area in Sumber Harapan Village, Sambas Regency resulted in a multi-mass area which includes gallery buildings, management offices, food courts and prayer rooms.